Spatial analysis of measles cases and vaccination coverage in the Somali region, eastern Ethiopia - Abdilahi Ibrahim Muse; Abdilahi Ibrahim Muse; Mahdi Yonis Kayat; Mohamed Harir Aden; Jemal Beksisa Shuramu; Shikur Mohammed; Musse Ahmed Ibrahim; Musse Ahmed Ibrahim; Binyam Mohammedbirhan Berhe; Ahmed Abdi Kalinle; Sahardiid Ali Abdilahi (Frontiers in Epidemiology)
BackgroundMeasles is a major public health concern that causes morbidity and mortality among children. In 2019, measles incidence reached its highest level in 23 years, with low measles containing vaccine dose one coverage playing a vital role. It can be prevented by two doses of the measles vaccine, either alone or in combination with measles-rubella (MR), which is a low-cost strategy for lowering morbidity and mortality among children.ObjectivesTo conduct spatial analysis of measles cases and vaccination coverage in the Somali region, Eastern Ethiopia.MethodsThis retrospective study was done by using public health emergency directorate measles data from 2022 to 2023 and four years (July 2019–July 2023) of vaccination data from district health information system version 2.36. After the data completeness and consistency were ensured, it was cleaned and recoded. STATA version 17 and QGIS version 3.38 software were used for the data analysis.ResultsFrom 2022 to 2023, the disease affected more than 5,930 people. The majority of the participants, 5,260 (88.7%), were under the age of 59 months, with 3,184 (53.7%) being male. Furthermore, the majority of residents were from Nogob 2,238 (37.7%), Erer 1,027 (17.3%), and Jarar 954 (16.1%). According to clinical symptoms, 5,930 (100%) of the cases had fever, cough, and rash, and more than two-thirds, 4,901 (82.6%), had complications. A measles vaccination coverage of 59.4% and a measles incidence of 0.087 per 100 people were found in the region.ConclusionsThis study found a very low measles vaccination coverage. Furthermore, Nogob, Erer, and Jarar zones showed the highest measles incidence rate, respectively. It is recommended to strengthen routine immunization services according to the national vaccination agenda, categorize, and reach unvaccinated children through catch-up vaccination campaigns. A concerted effort should be made to improve MCV2 coverage in hard-to-reach areas of the region. Special focus should be given to vaccine cold chain management in the zone and its districts with high vaccination coverage but also a high measles incidence rate. An investigation should be done into the associated factors of the higher incidence despite its vaccination coverage.